PRIORITAS PERBAIKAN PELAYANAN TRANSPORTASI MENGGUNAKAN METODE SERVQUAL - Andriana, Anna Dara; Handi, Rizky (Universitas Komputer Indonesia, 2020)
PT. Tunggal Jaya Transport is a company engaged in transportation services that has two types of services. They are bus rental and bus travel. Along with the development and spread of transportation services, companies are challenging to retain their customers because they did not know what to improve in the services they offer to customers. We can overcome this by analyzing service appraisals and priority improvements that can be made by the company so that it can maintain its competitiveness. Service assessment and service improvements are carried out using the servqual method. This method measures the quality of service using five dimensions: reliability, responsiveness, assurance, empathy, and physical evidence, to obtain a difference or gap in value can be analyzed further. Each size will be lowered back into a variable that fulfills and is related to what the company is doing. Each variable will be calculated the perceived value and the expected value to obtain the gap value. This gap value showed the priority of services that must be fixed by the company immediately. The results showed that the repair of bus vehicles had the highest gap value. The value identified that the company can prioritize bus service to have a highly competitive cost still. Key Words : Customer relationship management, services, servqual